Rheological and early age mechanical properties of 3D printed concrete containing copper heap leach residue as fine aggregate - Nusrat Jahan Mim; Anwar Hosan; Faiz Uddin Ahmed Shaikh; Prabir Kumar Sarker (Results in Engineering)
The utilization of mine waste as a fine aggregate in 3D printed concrete (3DPC) not only addresses the shortage of natural resources but also provides significant environmental benefits. This research investigates the feasibility of using copper heap leach residue (CHLR) as an alternative to fine aggregate in the 3DPC. The workability, rheological properties, buildability, hydration properties, and early-age mechanical strength of 3DPC incorporating varying dosages (0 %, 25 %, 50 %, 75 % and 100 %) of CHLR are evaluated. The findings reveal that increasing CHLR content leads to reduced flowability and faster fluidity loss, primarily due to CHLR’s rough surface texture, flaky morphology, and high-water absorption, which increase internal friction and disrupt particle packing. Despite this, appropriate dosages of high-range water-reducing admixtures and set accelerators ensured a consistent 45-minute printing window. Setting times shortened with higher CHLR dosages due to enhanced hydration kinetics, while buildability improved up to 75 % replacement, beyond which excessive pore formation hindered structural stability. Rheological measurements revealed higher yield stress and plastic viscosity, indicating enhanced thixotropy and interparticle interaction. The compressive strength is improved by 17 % at 75 % CHLR supported by reduced free water and denser microstructure but decreased at 100 % CHLR. Overall, the study concludes that the CHLR can be effectively used as a partial replacement of natural sand in 3D printed concrete, optimizing both buildability and mechanical properties, especially at up to 75 % replacement.